Avrupa Birliği ve Türk rekabet hukuku kapsamında tam işlevsellik unsuru - Uluçlar, Önder Suat (İstanbul Bilgi Üniversitesi, 2016)
[Abstract Not Available]
Full-functionality according to EU and Turkish competition law